Effect of Fetal Calf Serum (FCS) Versus Polyvinylpyrrolidine (PVP) on in vitro Maturation of Oocytes Retrieved by Ovum Pick-up (OPU) in Sahiwal Cows - Singh, Khushpreet; Singh, Narinder; Kaur Mavi, Gurjot; Honparkhe, Mrigank; Shekhar, Apoorva; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2025)
The experiment was conducted to compare the effect of supplementation of fetal calf serum (FCS) versus polyvin ylpyrrolidine (PVP) on in vitro maturation (IVM) of the bovine oocytes collected by ovum pick-up (OPU) method.  Cumulus oocyte complexes (COC’s) obtained by follicular aspiration having at least a complete layer of cumulus cells  were randomly divided into two groups containing 10 replicates each of 10-12 oocytes. In vitro maturation of the COC’s  supplementation of 5% FCS showed (Mean±Std. Error, %) higher full expansion of cumulus cells (9.20±0.64, 90.20)  in comparison to 1% PVP (8.5±0.45, 81.73), though non-significant. On the other hand, COC’s showing intermedi ate expansion were significantly low (p
Keywords: Cumulus Oocyte Complexes (COCs); Fetal Calf Serum (FCS); In Vitro Maturation (IVM); Ovum Pick-up (OPU); Polyvinylpyrolidine (PVP)